PENTINGNYA PERENCANAAN PEMBELAJARAN YANG KREATIF DAN INOVATIF UNTUK PERKEMBANGAN ANAK USIA DINI - Abellia, Ninda; Abidin, Zainal; Purnomo, Eko; Pohan, Nur Khomisah (Program Studi Pendidikan Islam Anak Usia Dini, 2025)
Creative and innovative learning planning is a fundamental component in early childhood education to optimize the development and potential of children. This study aims to analyze the implementation of creative and innovative learning planning in early childhood education (PAUD) and its impact on children's development. This research uses a qualitative method with a field approach conducted at PAUD Rara, Payakabung Village, North Indralaya District. The research subjects consist of 16 children from Class B and one class teacher. Data collection was carried out through observation, interviews, and documentation, with data analysis using the Miles and Huberman model. The results show that the implementation of creative and innovative learning planning achieved an average success rate of 81.67%. This success is reflected in the increased active participation of children (90%), creativity of children (82%), and effectiveness of the use of learning media (80%). The study also identifies three main factors supporting the successful implementation: teacher competence, availability of facilities and infrastructure, and parental support.